Literature as Resistance: The Pragmatics of Ecological Advocacy in ‘Oil on Water’ by Helon Habila - Ogungbemi, Olarotimi (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This paper delves into the linguistic representation of environmental and human degradation in Helon Habila’s “Oil on Water,” a novel that interrogates the socio-ecological impact of oil exploration in Nigeria’s Niger Delta. By employing Critical Discourse Analysis and the Appraisal Framework, the study exposes how language not only reflects but also shapes the perceived reality of ecological destruction and social conflict. The analysis highlights how linguistic strategies in the novel depict the multifaceted relationship between the indigenous communities, the Nigerian government, and multinational oil companies, presenting a landscape marred by exploitation and marginalization. The research identifies the use of vivid descriptive language, metaphor, and narrative perspective to evoke a sensory experience of the Niger Delta’s plight. It illustrates the oil companies and government as neocolonial actors, revealing a complex interplay of power dynamics where the local population is trapped in a cycle of violence and ecological devastation. Habila’s work emerges as a form of literary militancy, advocating for social and ecological justice through a portrayal of the Niger Delta’s disrupted social structures and ravaged ecosystems. Through a close reading of “Oil on Water,” the paper argues that literature serves as a potent tool for environmental advocacy, with the potential to influence public perception and policy. Habila’s narrative technique and linguistic choices function as a call to action, aligning with ecocritical discourses that prioritize environmental sustainability and community autonomy. The study underscores the critical role of language in environmental literature, demonstrating its capacity to engage readers and prompt reflection on the urgent issues of ecological degradation and human suffering.